2011
DOI: 10.4028/www.scientific.net/ssp.181-182.3
|View full text |Cite
|
Sign up to set email alerts
|

Rolic<sup>®</sup> LCMO Photo Alignment Technology: Mechanism and Application to Large LCD Panels

Abstract: Abstract. Rolic® Light Controlled Molecular Orientation (LCMO) technology is the basis for todays advanced mass production technologies for large LCD-TV panel, high-resolution 3D patterned-retarders and high-resolution optical security devices. This fundamental technology allows an easy achievement of high resolution azimuthal LC-director patterns with defined bias angles, from homogeneous planar to homeotropic orientation, depending on the target application [1][2][3][4][5][6][7]. In addition to the control o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Still, the emergence of the tta' dimer configuration as the most stable suggests that antiparallel coupling of Trans molecules can be favoured: this indicates that the interpolymer linking by cycloaddition would be an efficient mechanism for realizing an alignment film. Experimentally, we have found that UV exposed thin films of typical photoalignment materials, are insoluble in common solvents 31 , starting from low exposure doses, which is a strong indication of inter-polymer cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…Still, the emergence of the tta' dimer configuration as the most stable suggests that antiparallel coupling of Trans molecules can be favoured: this indicates that the interpolymer linking by cycloaddition would be an efficient mechanism for realizing an alignment film. Experimentally, we have found that UV exposed thin films of typical photoalignment materials, are insoluble in common solvents 31 , starting from low exposure doses, which is a strong indication of inter-polymer cross-linking.…”
Section: Discussionmentioning
confidence: 99%
“…The photo-alignment method LCMO [3,6] is used for obtaining the multi-domain structure, i.e., when cinnamate chromophores are irradiated obliquely by the linearly polarized UV light, the cinnamate chromophores arranging along the polarized UV light plane photo-crosslink by forming cyclobutane groups and form some kind of an anisotropy surface as shown in Fig. 1.…”
Section: Photo-crosslinking With Linearly Polarized Uv Lightmentioning
confidence: 99%
“…It took about two decades from the proposal of photo alignment methods [1][2][3] to the mass production of liquid crystal display panels utilizing the photo alignment technology. In 2008, Sharp UV 2 A® (Ultra Violet Induced Vertical Alignment) display mode [4,5] using Rolic® LCMO (Light Controlled Molecular Orientation) technology [6] was applied to LC-TV (Liquid Crystal Television) because of its excellent properties such as high contrast ratio, high transmittance, fast response and high production yield. After introduction of the UV 2 A technology into China, CEC Panda in Nanjing has successfully introduced the first Rolic ready-to-use photo alignment material into mass production in 2013.…”
Section: Introductionmentioning
confidence: 99%
“…It took about two decades from the proposal of photo alignment methods [1][2][3] to the mass production of liquid crystal display panels utilizing the photo alignment technology. In 2008, Sharp UV 2 A® (Ultra Violet Induced Vertical Alignment) display mode [4,5] using Rolic® LCMO (Light Controlled Molecular Orientation) technology [6] was applied to LC-TV (Liquid Crystal Television) because of its excellent properties such as high contrast ratio, high transmittance, fast response and high production yield. After that, the UV 2 A display mode has been widely used for several applications.…”
Section: Introductionmentioning
confidence: 99%